New combinations and a new name for including Nemum species in Bulbostylis (Abildgaardieae: Cyperaceae) - Larridon, Isabel; Goetghebeur, Paul; Roalson, Eric H. (Phytotaxa, 2019)
A recent study included the genus Nemum into Bulbostylis. The combinations made for Nemum spadiceum and Nemum megastachyum resulted in illegitimate names. Here, the epithet of the homotypic name Scirpus briziformis is used to make nomenclaturally correct combinations for both subspecies of Nemum spadiceum in Bulbostylis. Furthermore, Bulbostylis brunneoacuminata, nomen novum, is proposed to include Nemum megastachyum in Bulbostylis.